Improving University Students’ Learning Achievement Using an Interactive-Based E-Module of Translation Technology Through Online and Blended Learning - Sujarwo, Sujarwo; Hakim Yassi, Abdul; Abbas, Herawaty; Sahib, Harlinah (Universitas Muhammadiyah Semarang, 2024)
The rapid development of information technology has fundamentally changed the process of teaching English through the integration of network information technology into the curriculum, which has had a substantial impact on students' academic achievement. This study aims to investigate the effect of an interactive - based E-module of translation technology towards learning achievement through online and blended learning in two private universities in Makassar. This research used quasi-experimental method. Data analysis used Structural Equation Models – Partial Least Square (SEM - PLS) and SPSS 26 version with population was 135 and sample was 45 EFL students. Findings show that there was significant value is 0.888, which is higher than 0.05, which shows that there is no effect of providing interactive-based e-module of translation technology on students’ translation achievement through online learning. And based on the results of the paired sample t-test, the Sig. of 0.000 or smaller than 0.05 which indicates there is a significant difference between the pre-test and post-test results. It can be concluded that there is no significant effect of an interactive based e-module of translation technology toward learning achievement through online learning by using e-module and no using E-module of translation technology. Meanwhile, there is significant effect of an interactive based e-module of translation technology on learning achievement through blended learning.